Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis in China: Epidemiology, Management, Prognosis, and Outlook - Su-Fang Chen; Zhi-Ying Li; Ming-Hui Zhao; Min Chen (Karger Publishers, 2024)
Background: Increasing evidence indicates that clinicopathologic phenotypes and ANCA serotypes may differ ethnically and geographically. This review highlights the progress in the prevalence, pathogenesis, management, and outcomes of anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in China. Summary: AAV is not rare in China. Cumulative evidence has demonstrated a significant preponderance of microscopic polyangiitis (MPA) and myeloperoxidase (MPO)-ANCA AAV in China. Even in patients with granulomatosis with polyangiitis (GPA), there is a predominance of MPO-ANCA over proteinase 3 (PR3)-ANCA, presenting a unique subset. The pathogenesis of AAV is multifactorial, with the role of complement activation being highlighted during recent years. Treatment strategies for AAV in China have also been refined recently. A rapid tapering of glucocorticoids to minimize exposure has been recommended by the Chinese guidelines. Along with a better understanding of the disease, B cell-targeted therapy and complement-targeted therapy are developing. A considerable number of patients in China received rituximab treatment and achieved remission. However, infection risk and associated mortality still remain concerns. Therefore, less rituximab exposure should be considered and evaluated in Chinese AAV patients. Prognostic factors have been reviewed. Of note, along with improved outcomes, there is an increase of cardiovascular and malignant-related death, warranting specific care. Recently, a modified renal risk score model has been validated for early risk prediction in Chinese AAV patients. Moreover, emerging biomarkers for AAV, including complement components, have been identified in Chinese patients. Key Messages: There is a preponderance of MPA and MPO-ANCA in China. Treatment strategies for Chinese AAV patients generally align with those in western countries, and to some extent, less aggressive. Prognostic factors and emerging biomarkers for AAV in China have been identified. Further challenges include optimizing interventions, minimizing treatment-related comorbidities, improving disease monitoring, and enhancing life qualities of AAV patients.